NanoSen-AQM: From Sensors to Users - Lucas, Pedro; Silva, Jorge; Araujo, Filipe; Silva, Catarina; Gil, Paulo; Arrais, Joel P.; Coutinho, Daniel; Salgueiro, Pedro; Rato, Luis; Saias, Jose; et al. (International Journal of Online and Biomedical Engineering (iJOE), 2020)
With the raising of environmental concerns regarding pollution, interest in monitoring air quality is increasing. However, air pollution data is mostly originated from a limited number of government-owned sensors, which can only capture a small fraction of reality. Improving air quality coverage in-volves reducing the cost of sensors and making data widely available to the public. To this end, the NanoSen-AQM project proposes the usage of low-cost nano-sensors as the basis for an air quality monitoring platform, capa-ble of collecting, aggregating, processing, storing, and displaying air quality data. Being an end-to-end system, the platform allows sensor owners to manage their sensors, as well as define calibration functions, that can im-prove data reliability. The public can visualize sensor data in a map, define specific clusters (groups of sensors) as favorites and set alerts in the event of bad air quality in certain sensors. The NanoSen-AQM platform provides easy access to air quality data, with the aim of improving public health.